A pallid rainbow: toward improved understanding of avian influenza biology. (June 2016) - Harder, Timm; Stech, Jürgen; Abdelwhab, El-Sayed M; Veits, Jutta; Conraths, Franz J; Beer, Martin; Mettenleiter, Thomas C
Highly pathogenic avian influenza ('fowl plague') has been known since the late 19th century as a devastating infection in poultry but of concern primarily to farmers and veterinarians. Mostly sporadic outbreaks occurred and, except for one episode, wild birds were unaffected. This situation changed drastically by the recognition that avian influenza viruses exhibit zoonotic potential leading to fatal infections in mammals including humans. Moreover, highly pathogenic avian influenza gained access to highly mobile, migratory wild bird populations resulting in unprecedented intercontinental spread. The rapid evolution of avian influenza viruses, their adaption to novel hosts and the resulting change in epidemiology are of major concern. Recent advances in understanding influenza virus biology at the interface between wild birds-terrestrial poultry-livestock and humans are highlighted here.